Artigo de opinião como macrogênero: relações lógico-semânticas na perspectiva sistêmico-funcional - Farencena, Gessélda Somavilla (2015)
In this work, the main objective consists in analyzing the logical-semantic relations in the text organization in steps and phases, in opinion articles related to the New Brazilian Forest Code thematic and published by the „Observatório da Imprensa‟ website.Guided by this purpose, this research allies two theoretical approaches circumscribed in the Systemic Functional Linguistic (LSF): 1) the Systemic Functional Grammar (GSF) (HALLIDAY, 1985, 1994; HALLIDAY; MATTHIESSEN, 2004, 2014), from which we use the concept of context – of situation and culture – ,to delineate the registers of the texts, and the categories of the clause complex, to verify how the lexico-grammar does, in the level above the clauses, the communicative purpose instanced by the opinion articles and which logical-semantic relations are established in the text organization; 2) the Australian perspective of Genre and Register (R&GT) (EGGINS; MARTIN, 1999; EGGINS, 2004; MARTIN; ROSE, 2008; MARTIN, 2009; ROSE, 2011; ROSE; MARTIN, 2012), from which we adopt the categories for the genre description and analysis from the functionalist point of view from the School of Sydney. Defined the theoretical-analytical categories, we proceeded to the description and analysis of the register variables. (location, relation and manner)from the nine opinion articles which constitute the corpus. Knowing the situational contextsthatinvolve the texts, we undertook the lexicogrammar analysis, with the description of the clause complex, which allowed detailing the logical-semantic structure of the texts.After finishing this procedure, we conducted the identification of the Genre Schematic Structure (EEG). Once known the communicative purpose of texts, we identified the steps and phases that happen in each opinion article, as well as possible elementary genres that could be instantiated as genres embedded in the dominant genre, which correspond to the macro genre (WOODWARD-KRON, 2005). For the identification and delimitation of the steps and phases, and of the micro genres verified, we based in the logical- sematic relations that are stablished by clause complexes and simplexes in the text organization. This way, with the identification of EEG, we proceeded to the verification of the logical- sematic relations between the genre steps and phases and, in the cases the genre brought micro genres, we also verified the logical- sematic relations between the steps and phases of the dominant genre and the micro genres. This conjunct analysis, linking the categories of GSF and R&GT, demonstrated that the opinion articles analyzed can be seen as macro genres, in which the dominant genre is the exposition, from the family of argumentation, and the elementary relate genres (from the family of stories), interpretation (from the family of reaction to texts), descriptive report, compositional reports (from the family of reports) and historical report ( from the family of histories) work as micro genres embedded in the macro genre, completing it. Between the steps and phases of the macro genre and also among themselves and the micro genres, the text organization occurs mainly through the logical-sematic relations of extension (44,3%), intensification (37,7%) and elaboration (18%).Therewith, facing the communicative purpose of the macro genre, we concluded that the opinion articles are organized in a way to have a progression in terms of content, with an increase of information which develop what was presented before or with the counterpoint between sayings or other people‟s ideas and facts and the point of view of the writer, configuring an counter-argumentation strategy. Besides, in the search for the thesis defense, causal relations explicit reasons, purposes and concessions that aim to justify to the reader, the writer‟s point of view.With this purpose, exemplifications with facts and concrete situations are resources used by writers to constitute and organize in a logical semantic way, the steps, phases and micro genres that realize the genre exposition instantiated by the opinion articles analyzed.